Mental health literacy and its associated factors among traditional healers toward mental illness in Northeast, Ethiopia: A mixed approach study. - Tamrat Anbesaw; Amare Asmamaw; Kidist Adamu; Million Tsegaw (PLoS ONE, 2024)
Background Currently, the biggest issue facing the entire world is mental health. According to the Ethiopian Ministry of Health, nearly one-fourth of the community is experiencing any of the mental illness categories. Most of the cases were treated in religious and traditional institutions, which the community most liked to be treated. However, there were very limited studies conducted to show the level of mental health literacy among traditional healers. Aims The study aimed to assess the level of mental health literacy and its associated factors among traditional healers toward mental illness found in Northeast, Ethiopia from September 1-30/2022. Method A mixed approach cross-sectional study design was carried out on September 130, 2022, using simple random sampling with a total sample of 343. Pretested, structured questionnaires and face-to-face interviews were utilized for data collection. The level of Mental Health Literacy (MHL) was assessed using the 35 mental health literacy (35-MHLQ) scale. The semi-structured checklist was used for the in-depth interview and the FGD for the qualitative part. Data was entered using Epi-data version 4.6 and, then exported to SPSS version 26 for analysis. The association between outcome and independent variables was analyzed with bivariate and multivariable linear regression. P-values < 0.05 were considered statistically significant. Thematic analysis was used to analyze the qualitative data, and the findings were then referenced with the findings of the quantitative data. Results The findings of this study showed that the sample of traditional healers found in Dessie City scored a total mean of mental health literacy of 91.81 ± 10:53. Age (β = -0.215, 95% CI (-0.233, -0.05), p = 0.003, informal educational status (β = -5.378, 95% CI (-6.505, -0.350), p = 0.029, presence of relative with a mental disorder (β = 6.030, 95% CI (0.073, 7.428),p = 0.046, getting information on mental illness (β = 6.565, 95% CI (3.432, 8.680), p = <0.001, and mental health training (β = 4.889, 95% CI (0.379, 6.455), p = 0.028 were variables significantly associated with mental health literacy. Traditional healers provide a variety of explanations for the causes of mental illness, including biological, psychological, and supernatural ones. Conclusion The mean score of the Mental Health Literacy Scale (MHLS) is lower among traditional healers compared with other studies. Age, informal educational status, family history of mental illness, getting information on mental illness, and mental health training were significantly associated with mental health literacy. Therefore, different works to improve the levels of mental health literacy among traditional healers are essential.